Quantitative proteomics analysis reveals core and variable tick salivary proteins at the tick‐vertebrate host interface. Issue 15 (19th June 2022) - Bensaoud, Chaima; Tenzer, Stefan; Poplawski, Alicia; Medina, José María; Jmel, Mohamed Amine; Voet, Hanne; Mekki, Imen; Aparicio‐Puerta, Ernesto; Cuveele, Brent; Distler, Ute; Marini, Federico; Hackenberg, Michael; et al.
Abstract: Few studies have examined tick proteomes, how they adapt to their environment, and their roles in the parasite–host interactions that drive tick infestation and pathogen transmission. Here we used a proteomics approach to screen for biologically and immunologically relevant proteins acting at the tick‐host interface during tick feeding and, as proof of principle, measured host antibody responses to some of the discovered candidates. We used a label‐free quantitative proteomic workflow to study salivary proteomes of (i) wild Ixodes ricinus ticks fed on different hosts, (ii) wild or laboratory ticks fed on the same host, and (iii) adult ticks cofed with nymphs. Our results reveal high and stable expression of several protease inhibitors and other tick‐specific proteins under different feeding conditions. Most pathways functionally enriched in sialoproteomes were related to proteolysis, endopeptidase, and amine‐binding activities. The generated catalogue of tick salivary proteins enabled the selection of six candidate secreted immunogenic peptides for rabbit immunizations, three of which induced strong and durable antigen‐specific antibody responses in rabbits. Furthermore, rabbits exposed to ticks mounted immune responses against the candidate peptides/proteins, confirming their expression at the tick‐vertebrate interface. Our approach provides insights into tick adaptation strategies to different feeding conditions and promising candidates for developing antitick vaccines or markers of exposure of vertebrate hosts to tick bites.